Physical Activity, Nutritional Status, Physical Fitness - Tomczak, Andrzej (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Physical activity, nutritional status, and fitness are important predictors of public health and the well-being of society as a whole. They influence the preparedness to perform official duties and tasks in some professional specialties. They are also important factors leading to success in professional sport and sport for all. This supplement to the Special Issue "Physical activity, nutritional status and physical fitness" consists of articles on two main thematic fields. The first field is a series of articles in which Polish soldiers, policemen, and border guards were the research subjects. The research issues concerned the determination of the level of physical activity, problems related to overweight and obesity, adherence to dietary recommendations, and the determination of energy expenditure. The authors assessed the state of a given variable and examined the relationships between individual variables in order to find the regularities on the basis of which it was possible to develop recommendations for soldiers and officers and their superiors (makers). The presented works were carried out as part of a research project of the National Health Program. The second thematic field concerns the physical activity, nutritional status, and fitness of the general public. Interesting topics that were discussed include the index for diet assessment, the influences of some genes on obesity, and the effect of modified training based on the principles of CrossFit on the development of general physical fitness in a group of kickboxers. The study also includes a paper on a new physical fitness test (ACFT) in the US Army.